Self determination-based design to achieve acceptance of assisted living technologies for older adults. (December 2016) - Dupuy, Lucile; Consel, Charles; Sauzéon, Hélène
Abstract: Providing technological support to assist older adults in their daily activities is a promising approach to aging in place. However, acceptance is critical when technologies are embedded in the user's life. Recently, Lee et al. established a connection between acceptance and motivation. They approached motivation via the Self-Determination Theory (SDT): the capacity to make choices and to take decisions. This paper leverages SDT to promote a new design style for gerontechnologies that consists of principles and requirements. We applied our approach to develop an assisted living platform, which was used to conduct a six-month field study with 34 older adults. We show that self-determination is a determining factor of technology acceptance. Furthermore, our platform improved the self-determination of equipped participants, compared to the control group, suggesting that our approach is effective. As such, SDT opens up new opportunities for improving the design process of gerontechnologies. Highlights: Design objectives for assisted living technologies leveraging SDT. Development of an assisted living platform for older adults. Realization of a field study to evaluate the designed platform. Deployments show effective support of self-determination and technology acceptance.